กระบวนการพัฒนาคุณภาพในโรงพยาบาลที่ได้รับการรับรองคุณภาพ - จิตกิตมณี อัคฮาดศรี (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
The purpose of this Grounded Theory study was to explain the process of quality development for hospital accreditation (HA) at an accredited hospital. Study participants were 32 nurses involving nursing quality development for hospital accreditation. Data collection was employed by using in-depth interview, observation, and field-note. Study data were analyzed by using coding and constant comparative method. The study findings consisting 3 phases of nursing quality development for hospital accreditation were as follows: 1. Preparing phase. It was consisted of (1) applying to be the pilot hospital for HA, (2) transferring the concept of HA to others (3) accepting the HA concept (4) learning the HA concept and (5) refusing the HA concept, but improving nursing quality by using quality assurance. 2. Implementing phase consisted (1) finding things to improve (2)improving matters (3) increasing motivation (4) learning for more understanding the HA concept (5) exchanging the experiences of using HA and (6) integrating the concept of quality assurance for improving nursing service. 3. Evaluating for hospital accreditation phase consisted of (1) self-assessment, (2) internal survey and improvement )3) external survey and improvement (4) accepting the HA policy to improve overall hospital s quality (5) sending HA report to the institution of HA and (6) HA evaluation, and being an accredited hospital.